Wetland vegetation of the Tarsia Lake Regional Nature Reserve (Calabria, southern Italy) - Maiorca, Giovanni; Crisafulli, Alessandro; Puntillo, Domenico; Signorino, Giuseppe; Spampinato, Giovanni (Mediterranean Botany, 2020)
A phytosociological analysis of Tarsia Lake Regional Nature Reserve was carried out within a research project dealing with the vegetation of southern Italian wetlands. Twenty-four plant communities (19 associations and five communities not yet assigned to formal rank) were attributed to 17 alliances, 14 orders, and 11 classes. Most associations resulted as common in the Mediterranean area; however, as a response to the peculiarity of the local climatic and edaphic factors, some phytocoenoses were found as typical throughout central Europe but not observed in southern Italy, yet. Currently, this area is preserving a considerably interesting flora and vegetation for both naturalistic and phytogeographic reasons. Therefore, an appropriate monitoring and protection plan is needed in order to counteract the ongoing severe anthropogenic pressure.
Keywords: Calabria; southern Italy; Tarsia Lake; wetland vegetation